MENCAPAI PRODUKSI KAKAO BERKELANJUTAN DI INDONESIA - Ibnu, Muhammad (JURNAL AGRIBISAINS, 2022)
Indonesia has the potential to become a major exporter of cocoa in the world as well as to meet the needs of the domestic cocoa industry. However, the lack of availability of raw materials (cocoa beans) causes the processing industry to import cocoa beans from other countries. Indonesia has even been included in the five largest cocoa importing countries in the world. This raises questions about the sustainability of cocoa production in Indonesia. This research has two objectives. First, predicting the sustainability of cocoa production in Indonesia. Second, identify strategies or efforts that need to be done so that cocoa production in Indonesia can achieve a better level of sustainability. The first objective of the research was achieved by using quantitative methods, namely by analyzing trends in secondary data (from FAOSTAT) related to cocoa production, planted area, and cocoa productivity as well as cocoa exports and imports. The second objective of the research is achieved by reviewing the literature, especially reviewing the results of empirical research (and various publications by cocoa-related institutions) to identify potential strategies in order to improve the sustainability of Indonesian cocoa production. The results showed that productivity problems have a high level of urgency to be overcome. If not addressed, there is a possibility that Indonesia will become a net cocoa importer in the future (imports are greater than exports). Strategies to increase the sustainability of Indonesian cocoa production need to focus on increasing productivity through the use of superior cocoa seeds, focus on specific support for farmers' livelihoods, focus on improving the supporting environmental instruments that are still lacking (such as access to finance and inputs, facilities and infrastructure) rural areas, capacity building of farmer organizations, and extension services) and focus on the existence of strong institutions to ensure the functioning of partnerships between farmers/farmers' organizations and other parties.